Evaluating the Impact of Business License Deregulation (Sunset Policy) on Service Sector Startup Formation - Nita Hasnita; Rachmawati; Nur Halimah Siahaan; Sofa Marwah; Kusman Paluala (CV. Get Press Indonesia, 2025)
The complexity of business licensing significantly impedes startup creation, particularly in the vital service sector. This study evaluates Indonesia's deregulation impact (the Online Single Submission (OSS) system and the sunset clause mechanism) on service sector startup formation during 2018–2024 using a mixed-methods approach. Quantitative analysis (Difference-in-Differences) of official data, confirmed for validity and reliability, shows a robust 15% increase in startup formation rates post-policy, with the strongest effects observed in digitally mature urban areas. Qualitative findings from interviews highlight persistent challenges, including regional implementation inconsistencies and administrative hurdles. The interpretation is that deregulation, supported by effective digital infrastructure, successfully fosters entrepreneurship. However, complementary capacity building and regulatory harmonization are essential for equitable distribution of benefits. This research contributes empirical micro-level evidence for policy guidance in emerging markets.